Assessing the use of remotely sensed surface water flux to estimate net groundwater storage change in an aquifer predominantly used for irrigation - Cindy Viviers; Michael van der Laan (Agricultural Water Management)
In intensely irrigated regions, effective cultivation and water use monitoring is crucial to ensure sustainability. Using the Steenkoppies Dolomitic Compartment (South Africa) as a case study, this study proposed a novel approach to monitor active cultivation, crop and net irrigation water use, and net groundwater storage (GWS) changes. The method addresses the limitations of annual land use land cover datasets and reliance on local ground-based data, enabling higher spatio-temporal Earth observation monitoring for intensively irrigated, groundwater-dependent areas. Remotely sensed data can estimate actual evapotranspiration (ETa) across various land cover types, but application for crop and irrigation water use monitoring specifically, requires integration with datasets identifying actively cultivated areas. A Random Forest classifier, trained on seasonal Sentinel-2 composites to capture crop phenological changes, was used to identify cultivated areas in monthly composites. These cultivated areas were integrated with WaPOR (Water Productivity Open Access Portal) ETa data to estimate monthly crop water use, while the difference between ETa and precipitation provided estimates of monthly surface water flux and net irrigation water use. Comparing surface water flux with net GWS changes offered a holistic, near real-time view of water demand and aquifer status at a monthly temporal resolution and a spatial resolution of 250 m. The study concluded that the irrigated cropped area expanded by 14 % since 2012, reaching 6 065 ha in 2021. The WaPOR-based crop water use estimates concluded a 250–300 mm shortfall compared to crop model estimates. The deficits between mean annual precipitation (652–733 mm yr−1) and the WaPOR-based mean annual irrigated crop water use (1 090 mm yr−1) over 6 065 ha equate to 21.7 Mm³ yr−1 and 26.6 Mm³ yr−1, aligning with the literature groundwater abstraction estimates exceeding 20 Mm³ for irrigation. Using the pixel-based, sum of monthly net irrigation estimates, however, even when factoring in a precipitation efficiency of 70 % and an irrigation efficiency of 80 %, the WaPOR-based net irrigation water use was estimated at only 12.7 Mm³ yr−1 for 2018/19 and 9.3 Mm³ yr−1 for 2019/20. The comparison of surface water flux with net GWS and precipitation confirmed that irrigated cultivation is the primary groundwater user, and that groundwater abstraction peaks during low precipitation periods, with precipitation being the main aquifer recharge source. Surface water flux proved a reliable proxy for monitoring and predicting the impact of irrigation on GWS levels during dry seasons. The cultivation and net irrigation intensity maps can be essential for strategising regulatory efforts and monitoring compliance with groundwater mitigation measures.